2020
DOI: 10.1177/2280800020926653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet and moisture action on biodegradable polymers and their blend

Abstract: In this work, the suitability of polylactic acid (PLA), polybutylene adipate terephthalate (PBAT) and PBAT/PLA blend samples to outdoor applications were investigated in terms of mechanical, morphological and visual properties in presence of ultraviolet action and water, finding that PLA in particular can be actually considered for such applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The reason for the drastic reduction of light transmission in the samples with 0% and 2% by weight of CaCO 3 can be attributed to the rapid yellowing of the matrix. [ 29 ] Indeed, when the sample changes from transparent to yellow, the polymer absorbs more visible light in the blue range, reducing the total light transmitted through the sample. In the case of 5%, the highest transmittance values are due to a minimization of yellowing.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the drastic reduction of light transmission in the samples with 0% and 2% by weight of CaCO 3 can be attributed to the rapid yellowing of the matrix. [ 29 ] Indeed, when the sample changes from transparent to yellow, the polymer absorbs more visible light in the blue range, reducing the total light transmitted through the sample. In the case of 5%, the highest transmittance values are due to a minimization of yellowing.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of the viscosity must be, then, correlated with an increase of the molecular weight or with a formation of some cross-links or some branching during the reprocessing. PBAT is, indeed, prone to form crosslinks during degradation [ 19 , 20 , 21 , 33 ], and the branching is the first step in forming cross-linked structures. No cross-links were revealed for the PLA.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work [ 33 ], it was demonstrated that photoxidation of PBAT can lead to different levels of cross-linking, depending on the environmental conditions. In particular, when photooxidation was carried out with a condensation cycle, cross-linking was lower than that measured when photooxidation was carried out without a condensation cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation phenomena are mainly due to the hydrolysis of the macromolecular chains with a severe decrease of molecular weight [ 9 , 10 , 11 ]. In addition, the presence of moisture strongly modifies the mechanical properties [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [ 13 ], we demonstrated how the presence of moisture significantly affects the mechanical properties of biodegradable polyesters subjected to UV irradiation.…”
Section: Introductionmentioning
confidence: 99%